Qawaid Learning Through Prezi Media and The Effectiveness of Maharah Qira'ah in Distance Learning - Daynesty, Helendya; Saputra, Prayoga; Rasyid, Ifkar (Borneo Journal of Language and Education, 2024)
21st-century learning requires the use of innovative media such as Prezi to deliver material in an engaging way, especially in facing the challenges of distance learning. In learning Arabic, understanding qawaid (Arabic rules) is important to form a strong basis for language understanding, especially in reading ability (maharah qira'ah). Learning media such as Prezi can help improve student’s understanding of qawaid and Arabic reading skills, as well as provide effective solutions in the context of distance learning. The aim of this research is to test the effectiveness of Prezi media in conveying qawaid al-lughah al-arabiyyah material and its impact on increasing student’s maharah qira'ah. This research methodology uses a quantitative approach with a quasi-experiment design, where the experimental and control classes are divided based on certain criteria. The results of data analysis using the Independent Sample T-Test showed significant differences between the post-test learning outcomes of the experimental class which used Prezi media and the control class. Learning qawā'id through Prezi media is effective in increasing the mahārah qirā'ah of class XI students at MAN Insan Cendikia Padang Pariaman, with the experimental class's N-Gain Score reaching 58%, quite effective. However, it is necessary to develop Prezi for Arabic fonts. It is recommended that future research measure teachers' readiness to use online learning media. Prezi media is important in distance learning, highlighting the importance of choosing the right media. In conclusion, the use of Prezi media in qawaid learning has the potential to increase student’s understanding and proficiency in Arabic, but needs further adaptation and development to maximize its benefits in a distance learning context.